Strengthening Sharia Governance and Global Competitiveness through Regulation and Supervision: Penguatan Tata Kelola Syariah dan Daya Saing Global melalui Regulasi dan Pengawasan - Imroatus Sholikhah; Lisa Marsela; Nugroho Mukti Syailendra; Naufal Luthfi Alifa (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2026)
Although Islamic financial institutions should ideally implement governance based on the principles of fairness, transparency, and accountability in accordance with Islamic values, the reality of practice shows various structural and institutional obstacles that hinder the achievement of optimal and substantive sharia governance. Therefore, this study aims to analyze how regulation and supervision can strengthen the governance of Islamic financial institutions to be adaptive, accountable, integrated, and responsive to global dynamics, without losing Islamic values as a basis. This study employs a qualitative method using a structured literature review approach with systematic and critical analysis. The results show that: (1) the harmonization of national regulations and international standards supports the stability, credibility, and competitiveness of the industry; (2) standardization and supervision improve accountability and transparency while simultaneously mitigating systemic risks and reducing information asymmetry; (3) the implementation of Islamic value-based Good Corporate Governance strengthens internal governance and enhances the independence and effectiveness of sharia supervisory boards, leading to both formal and substantive compliance; (4) the role of the state and financial authorities is strategic in encouraging innovation, inclusion, and the sustainable strengthening of Islamic financial institutions at both national and global levels.